2021
DOI: 10.1177/23247096211013193
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Double Antibody-Positive Rapidly Progressive Glomerulonephritis: A Therapeutic Challenge

Abstract: Crescentic glomerulonephritis, also known as rapidly progressive glomerulonephritis, is a syndrome characterized by progressive and rapid deterioration of renal function over the course of weeks to months. Oliguria, hematuria, azotemia, and hypertension are characteristic features of this condition. Crescentic glomerulonephritis is further classified according to the staining pattern on immunofluorescence. In rare instances, a mixed pattern of injury is encountered as in the case of double antibody-positive ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Upon further review of double-positive ANCA and anti-GBM cases, none have reported the use of rituximab as a primary induction therapy. All cases include glucocorticoids, plasmapheresis, and cyclophosphamide with or without rituximab as an "add-on" therapy [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Upon further review of double-positive ANCA and anti-GBM cases, none have reported the use of rituximab as a primary induction therapy. All cases include glucocorticoids, plasmapheresis, and cyclophosphamide with or without rituximab as an "add-on" therapy [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…По данным разных авторов, 10-40 % анти-ГБМ положительных пациентов также имеют положительные АНЦА, а у 5-14 % АНЦА-поло жи тельных пациентов выявляют анти-GBM антитела [8,10,[12][13][14]. Этот так называемый двойной антитело-положительный фенотип нередко обусловливает атипичную клиническую картину, что приводит к задержке установления правильного диагноза, связан с плохими исходами -частыми обострениями и высокой смертностью [9,11,15]. Механизм и клиническое значение двойного антитело-положительного фенотипа остаются неясными.…”
unclassified
“…Некоторые авторы считают, что АНЦА-опосредованный почечный васкулит может играть роль в инициации образования антител против ГБМ, вызывая повреждение эндотелия и демаскируя эпитопы коллагена [15,16]. Случаи БПГН, положительные по двум вариантам антител, не только обусловливают агрессивное течение анти-ГБМ заболевания, но и высокий риск рецидивов, связанных с АНЦАваскулитом [9]. Для наиболее полного знакомства с данной проблемой доступен систематический обзор [17].…”
unclassified
See 1 more Smart Citation